city jobs - BENAMAR, Samia (Social Sciences Journal)
Cities gained importance with the emergence of the industrial revolution, where the emergence of cities was mainly associated with industry. The capitalist industrial system attributed to cities the importance they had in the Roman era, but at the end of the Roman era and the beginning of the Middle Ages, cities went through a period of "European darkness", that is, they witnessed a commercial recession, political weakness, and the loss of cities Its importance is greater with the emergence of the feudal system, which did not consider the city as its center, but rather the village or agriculture became the pillars of the feudal system, and in fact the emergence of the bourgeoisie had led to the weakening of the feudal system and the emergence of a new social structure, accompanied by the development of professions, crafts and industry in the city to bring The causes of urban activity are trade, transportation, industry and various services (1), and thus the capitalist industrial system appeared and the city regained its importance again.